Isotoosendanin inhibits triple-negative breast cancer metastasis by reducing mitochondrial fission and lamellipodia formation regulated by the Smad2/3-GOT2-MYH9 signaling axis - Zhang Jing-nan; Zhang Ze; Huang Zhen-lin; Guo Qian; Wu Ze-qi; Ke Chuang; Lu Bin; Wang Zheng-tao; Ji Li-li (Acta Pharmacologica Sinica, 2024)
Triple-negative breast cancer (TNBC) is incurable and prone to widespread metastasis. Therefore, identification of key targets for TNBC progression is urgently needed. Our previous study revealed that isotoosendanin (ITSN) reduced TNBC metastasis by targeting TGFβR1. ITSN is currently used as an effective chemical probe to further discover the key molecules involved in TNBC metastasis downstream of TGFβR1. The results showed that GOT2 was the gene downstream of Smad2/3 and that ITSN decreased GOT2 expression by abrogating the activation of the TGF-β-Smad2/3 signaling pathway through directly binding to TGFβR1. GOT2 was highly expressed in TNBC, and its knockdown decreased TNBC metastasis. However, GOT2 overexpression reversed the inhibitory effect of ITSN on TNBC metastasis both in vitro and in vivo. GOT2 interacted with MYH9 and hindered its binding to the E3 ubiquitin ligase STUB1, thereby reducing MYH9 ubiquitination and degradation. Moreover, GOT2 also enhanced the translocation of MYH9 to mitochondria and thus induced DRP1 phosphorylation, thereby promoting mitochondrial fission and lamellipodia formation in TNBC cells. ITSN-mediated inhibition of mitochondrial fission and lamellipodia formation was associated with reduced GOT2 expression. In conclusion, ITSN prevented MYH9-regulated mitochondrial fission and lamellipodia formation in TNBC cells by enhancing MYH9 protein degradation through a reduction in GOT2 expression, thus contributing to its inhibition of TNBC metastasis.